ADAMTS13 regulation of VWF multimer distribution in severe COVID‐19. (20th June 2021) - Ward, Soracha E.; Fogarty, Helen; Karampini, Ellie; Lavin, Michelle; Schneppenheim, Sonja; Dittmer, Rita; Morrin, Hannah; Glavey, Siobhan; Ni Cheallaigh, Cliona; Bergin, Colm; Martin‐Loeches, Ignacio; Mallon, Patrick W.; et al.
Abstract: Background: Consistent with fulminant endothelial cell activation, elevated plasma von Willebrand factor (VWF) antigen levels have been reported in patients with COVID‐19. The multimeric size and function of VWF are normally regulated through A Disintegrin And Metalloprotease with ThrombSpondin Motif type 1 motif, member 13 (ADAMTS‐13)‐‐mediated proteolysis. Objectives: This study investigated the hypothesis that ADAMTS‐13 regulation of VWF multimer distribution may be impaired in severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) infection contributing to the observed microvascular thrombosis. Patients and Methods: Patients with COVID‐19 ( n  = 23) were recruited from the Beaumont Hospital Intensive Care Unit (ICU) in Dublin. Plasma VWF antigen, multimer distribution, ADAMTS‐13 activity, and known inhibitors thereof were assessed. Results: We observed markedly increased VWF collagen‐binding activity in patients with severe COVID‐19 compared to controls (median 509.1 versus 94.3 IU/dl). Conversely, plasma ADAMTS‐13 activity was significantly reduced (median 68.2 IU/dl). In keeping with an increase in VWF:ADAMTS‐13 ratio, abnormalities in VWF multimer distribution were common in patients with COVID‐19, with reductions in high molecular weight VWF multimers. Terminal sialylation regulates VWF susceptibility to proteolysis by ADAMTS‐13 and other proteases. We observed that both N‐ and O‐linked sialylation were altered in severe COVID‐19. Furthermore, plasma levels of the ADAMTS‐13 inhibitors interleukin‐6, thrombospondin‐1, and platelet factor 4 were significantly elevated. Conclusions: These findings support the hypothesis that SARS‐CoV‐2 is associated with profound quantitative and qualitative increases in plasma VWF levels, and a multifactorial down‐regulation in ADAMTS‐13 function. Further studies will be required to determine whether therapeutic interventions to correct ADAMTS‐13‐VWF multimer dysfunction may be useful in COVID‐microvascular thrombosis and angiopathy.